Kesan Penggunaan Teknik Pengurusan Tekanan terhadap Pencapaian Akademik (CGPA) Kajian Kes : Pelajar UiTM Arau, Perlis - Rosni, Abdullah (2003)
The aim of this study in general is to see the effect of stress management techniques on academic achievement (CGPA) of final semester students of UiTM Arau, Perlis. The specific objective of this study is to see whether students who practice stress management techniques obtained higher CGPA than those who do not practice stress management techniques. This is done by looking at the corelation between stress management techniques of time management, social support, exercise, relaxation and CGPA. The study used questionnaires which had been used by Whetten, Cameron and Woods (1996) for time management, Freed (1984) for social support and Trockel, Barnes and Egget (2000) for exercise and relaxation. Cronbach alpha values of this questionnaire are 0.84 for time management, 0.895 for social support and exercise and 0.73 for relaxation. The result of this study showed that there was no significant co-relations between time management, social support, exercise, relaxation and CGPA of final semester students of UiTM Arau. Therefore, the study concluded that students who practiced stress management techniques do not necessarily obtained higher CGPA than those who do not. However, results of this study showed that there are significant differences in the usage of these stress management techniques between males and females and between diploma and degree level students.